INSIGHT responsive parenting intervention reduces infant's screen time and television exposure - Elizabeth L. Adams; Michele E. Marini; Jennifer Stokes; Leann L. Birch; Ian M. Paul; Jennifer S. Savage (BMC, 2018)
Abstract Background Sedentary behaviors, including screen time, in childhood have been associated with an increased risk for overweight. Beginning in infancy, we sought to reduce screen time and television exposure and increase time spent in interactive play as one component of a responsive parenting (RP) intervention designed for obesity prevention. Methods The Intervention Nurses Start Infants Growing on Healthy Trajectories (INSIGHT) study is a randomized trial comparing a RP intervention with a safety control intervention. Primiparous mother-newborn dyads (N = 279) were randomized after childbirth. Research nurses delivered intervention content at infant ages 3, 16, 28, and 40 weeks and research center visits at 1 and 2 years. As one component of INSIGHT, developmentally appropriate messages on minimizing screen time, reducing television exposure in the home, and promoting parent-child engagement through interactive play were delivered. Mothers self-reported their infant's screen time at ages 44 weeks, 1, 1.5, 2 and 2.5 years; interactive play was reported at 8 and 20 weeks and 2 years. Results More RP than control parents reported their infants met the American Academy of Pediatrics' no screen time recommendation at 44 weeks (53.0% vs. 30.2%) and at 1 year on weekdays (42.5% vs. 27.6%) and weekends (45.5% vs. 26.8%), but not after age 1 year. RP mothers and RP children had less daily screen time than controls at each time point (p ≤ 0.01). Fewer RP than control group mothers reported the television was ever on during infant meals (p < 0.05). The frequency of tummy time and floor play did not differ by study group; approximately 95% of infants spent time in restrictive devices (i.e. swing) at 8 and 20 weeks. At 2 years of age, there were no study group differences for time children spent in interactive play. Conclusion From infancy to early childhood, the INSIGHT RP intervention reduced screen time and television exposure, but did not increase the frequency or amount of interactive play. Trial registration clinicaltrials.gov NCT01167270. Registered on 21 July 2010.